Chemical constituents of the different anatomical parts of the oil palm (Elaeis guineensis) for their sustainable utilization - Saka, S.; Munusamy, M.V.; Shibata, M.; Tono, Y.; Miyafuji, H. (2008)
As the worldwide production of palm oil (Elaeis guineensis) is increasing, concomitant wastes of unutilized parts of the oil palm are also increasing. Thus, effective utilization of these wastes is expected. In this paper, therefore, the chemical composition of cellulose, hemicellulose, lignin and other minor cell wall components was studied for six different anatomical parts of the oil palm such as trunk, frond, mesocarp, endocarp (shell), kernel cake and empty fruit bunch (EFB). As a result, it was shown that cellulose is in a range between 20-40wt% with hemicellulose being 10-35wt%, whereas lignin in a range between 23-52wt%. More in detail, the shell contained the highest lignin about 52wt% but the kernel cake no lignin, while the rest in a range between 23-35wt%, being composed of guaiacyl and syringyl moieties without p-hydroxyphenyl propane residue. This is very similar to the hardwood-type lignin, rather than softwood-type lignin. On hemicellulose, mannan was rich in kernel cake, while glucuronoxylan rich in the other parts, with 1.8-8.5 xyloses per one uronic acid. Consequently, oil palm is not a good material for ethanol fermentation by yeast (Saccharomyces cerevisiae) because of high pentosan and low hexosan contents. As a minor component, inorganic constituents were also studied from the ash by scanning electron microscopy equipped with energy dispersive X-ray analysis (SEM-EDXA). As a result, K, Si, Na, Ca, S, P and Mg were found as elements in all parts of the oil palm studied. Particularly, Si and K were abundant in the trunk, shell, mesocarp and kernel cake, while the frond and kernel cake contained, respectively, K, Ca and P in a large quantity. The elements of Cl, Fe and Al were, however, detected only in some parts. These elements found are important and prerequisite for the healthy growth of the oil palm. Therefore, it may be concluded that, upon the whole utilization of the oil palm, inorganic constituents found in this study must be returned to the plantation site. These lines of information are useful for the efficient utilization of the whole parts of the oil palm which is necessary for the sustainable development of the biomass resources.